The Multi-representation-based Module Development to Improve the Metacognition of Circular Motion - Indraswari, Alfisyahr Silvandani; Budiarti, Indah Slamet; Bo, Bonefasius Yanwar (Berkala Ilmiah Pendidikan Fisika, 2024)
This study describes the analyses of multi-representation-based teaching modules' necessity, reliability, and practicality to improve the metacognition of circular motion material. This study employed R&D (Research and Development) with Borg and Gall's model. The population consisted of the students at Public Senior High School 1 Jayapura. The samples were 26 students from the ninth grade of Public Senior High School 1 Jayapura, which were determined by cluster random sampling. The data were collected through interviews, observation, documents, expert validation, questionnaires of students’ responses, and pretest-posttest. The data was analyzed using expert validation results, student-response questionnaire analysis with the Likert scale, and N-gain analysis from the pretest-posttest. The results indicated that the teaching module implemented was not pertinent to the student's requirements. Nevertheless, the devised teaching module was practical and reliable, with a 90.16% and 77.21% success rate. Consequently, the researchers determined that the module developed based on the multi-representation of circular motion could improve the student's metacognition. In this study, researchers developed a multi-representation-based module that had the potential to enhance students' metacognitive knowledge.